A corpus-based study on China's international counterterrorism discourse (2001-2021) - Chen, Jin (2023)
This thesis seeks to investigate the characteristics of China's international counterterrorism discourse. It argues that China discursively represents terrorism and counterterrorism through its lens of strategic culture. Drawing upon Johnston's strategic culture paradigm, this thesis analyses China's international counterterrorism discourse in three areas: discourse on terrorism, discourse on counterterrorism war, and discourse on international counterterrorism cooperation. Within each area, discursive themes, strategies, and prosodies are analysed to reveal the characteristics of China's international counterterrorism discourse, and strategic cultural explanations are carried out to interpret the findings through the lens of Chinese strategic culture. To do so, it adopts a corpus-based approach to carry out discourse analysis. Specialised corpora, which include the Terrorism Corpus, the Counterterrorism War Corpus, and the Counterterrorism Cooperation Corpus, are constructed based on texts collected from People's Daily. The analysis reveals that: terrorism is represented as an absolute, common, and severe threat to the international community but also a threat that is possible to manage at its roots; the use of force is represented as a path of low efficacy in dealing with the terrorism threat; international counterterrorism cooperation is represented as the preferred approach in international counterterrorism. The findings suggest that the representation of terrorism and counterterrorism corresponds with China's strategic cultural perceptions and preferences in dealing with national threats. First, anything that poses challenges to China's national sovereignty and territorial integrity is regarded as a core threat. But at the same time, China is also predisposed to the perception that conflict is not zero-sum in nature and is possible to be resolved with appropriate measures. Second, as a less efficacious approach to dealing with threats, the use of force is self-defence in nature and should conform to international norms and moral standards. Third, the existing international system and multilateralism should be upheld in dealing with international security issues.